Cytokine Profile in Aqueous Humor of Patients With Ocular Toxocariasis - Jiang, Zhaoxin; Sun, Limei; Ding, Xiaohu; Zhang, Ting; Li, Songshan; Ding, Xiaoyan (Frontiers in Medicine, 2022)
Purpose: Ocular toxocariasis (OT) is a vision-threatening disease with a largely unknown intraocular pathogenesis. Herein, we determined the cytokine expression profile in aqueous humor (AH) of patients with OT. Methods: This is a retrospective case-control study of cytokine levels in AH of patients with OT and uveitis and control subjects. Thirty samples from eyes with OT, 23 from eyes with non-OT uveitis, and 25 from eyes with age-related cataract were analyzed using a multiplexed magnetic bead immunoassay. Thirty-one cytokines were detected and classified into 5 categories: T-helper type 1 (Th1) -associated cytokines, Th2-associated cytokines, Th17 cytokine, proinflammatory mediators, and growth factors. Results: In the 31 cytokines, 9 cytokines were undetectable, including IL-1a, IL-1b, IL-2, IL-3, IL-12p70, IL-17A, TGF-a, TNF-β and IFN-g. From the 22 cytokines, 13 exhibited significantly increased expression in the OT group than in the control group, including TNF-a, IFN-a2, IL-4, IL-5, IL-6, IL-9, IL-10, IL-13, sCD40L, PDGF-AA, PDGF-AB/BB, FLT3l and EGF. There were 5 cytokines exhibited significantly increased expression in the OT group than in non-OT group, including IL-5, IL-9, IL-10, IL-13 and PDGF-AA. There was no significantly decreased expression in any cytokines in the OT group when compared with control or non-OT groups. To the 5 cytokines that showed significant difference in OT group alone, IL-10 and IL-13 exhibited more than 13-fold increase, and IL-5 showed the most obvious as 27-fold increase in OT patients, when compared with that in control group. Conclusions: The cytokine profile expression in aqueous humor from patients with ocular toxocariasis was investigated, and our findings suggest that Th1 and Th17 cytokine responses are not enhanced, whereas the cytokine status was polarized toward a Th2 response. Our findings also suggest the involvement of IL-5, IL-10 and IL-13 in the immunopathogenesis of ocular toxocariasis.